Sintesis Biodiesel Dari Minyak Biji Nyamplung (Calophyllum Inophyllum) Menggunakan Katalis Geopolimer Berbasis Kaolin - Al Qarni Putra; Edy Saputra; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Biodiesel is one of alternative energy which replace the fossil fuel as the product of transesterification of vegetable plants. Whole this time, the process of making biodiesel using homogeous catalyst NaOH or KOH which produce soap and hard to separate biodiesel product using catalyst as its disadvantages. Therefore, by using heterogen catalyst, researcher start to develop it using catalyst geopolymer in the oil of calophylluminophyllum seed. The objective of this research is making biodiesel from the oil of calophylluminophyllum seed, knowing the influence of geopolimer ctalyst toward the number of biodiesel that has been produced, knowing the best condition of making biodiesel and also identifying the charateristics of calophylluminophyllum seed oil. This research starts from raw material preparation which include mixing, heating, and refinement. Furthermore, degumming the calophylluminophyllum seed oil to remove impurities contained in the oil. The transesterification process of oil has done in different level of speed i.e 200, 300, 400 rpm respectively and various catalyst concentration i.e 1%, 2%, 3% respectively at methanol of oil mole ratio 9: 1 and the reaction temperature of 60 °C and a reaction time of 120 minutes. From the result was obtained that the highest biodiesel of 92,14% at the stiring speed 400 rpm with 2% concentration geopolymercatalyst. Physical characterization have done such as density 878 kg/m3, kinematic viscosity3,67 mm2/s, acid number 0,46mg-KOH/g biodiesel and flash point 137°C respectively according to the standard of Indonesian biodiesel (SNI 7182:2015).Keywords :Biodiesel, calohyllum inophyllum seed oil, geopolymer